Insertional Inactivation of Methylmalonyl Coenzyme A (CoA) Mutase and Isobutyryl-CoA Mutase Genes in Streptomyces cinnamonensis: Influence on Polyketide Antibiotic Biosynthesis - Vrijbloed, Jan W. (American Society for Microbiology, 1999)
The coenzyme B(12)-dependent isobutyryl coenzyme A (CoA) mutase (ICM) and methylmalonyl-CoA mutase (MCM) catalyze the isomerization of n-butyryl-CoA to isobutyryl-CoA and of methylmalonyl-CoA to succinyl-CoA, respectively. The influence that both mutases have on the conversion of n- and isobutyryl-CoA to methylmalonyl-CoA and the use of the latter in polyketide biosynthesis have been investigated with the polyether antibiotic (monensin) producer Streptomyces cinnamonensis. Mutants prepared by inserting a hygromycin resistance gene (hygB) into either icmA or mutB, encoding the large subunits of ICM and MCM, respectively, have been characterized. The icmA::hygB mutant was unable to grow on valine or isobutyrate as the sole carbon source but grew normally on butyrate, indicating a key role for ICM in valine and isobutyrate metabolism in minimal medium. The mutB::hygB mutant was unable to grow on propionate and grew only weakly on butyrate and isobutyrate as sole carbon sources. (13)C-labeling experiments show that in both mutants butyrate and acetoacetate may be incorporated into the propionate units in monensin A without cleavage to acetate units. Hence, n-butyryl-CoA may be converted into methylmalonyl-CoA through a carbon skeleton rearrangement for which neither ICM nor MCM alone is essential.